Remittances and well-being among rural-to-urban migrants in China - Alpaslan Akay; Corrado Giulietti; Juan David Robalino; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2012)
The main objective of this paper is to propose a systematic approach to empirically analyse the effect of remittances on the utility of migrants, as proxied by their subjective well-being (SWB). Using data from a new survey on China (RUMiC), we estimate models in which a measure of subjective well- being is regressed on the level of remittances, and we find a sizeable positive correlation. The effect of remittances on well-being varies with the socio- economic characteristics of migrants, migration experience and the diversity of family arrangements. As a complementary objective, we use SWB measures to elicit the motivations behind remittances and find evidence that both altruistic (such as pure altruism and reciprocity) and contractual motivations (such as co-insurance and investment) are at work among rural-to-urban migrants in China.
Keywords: J61; D63; D64; I3; 330; migrants; subjective well-being; remittances; Rücküberweisung (Migranten); Landflucht; Binnenwanderung; Zufriedenheit; China